PENGARUH KEPUASAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI BLUD RUMAH SAKIT IBU DAN ANAK PROVINSI ACEH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING: Pengaruh Kepuasan Kerja, Organizational Citizenship Behavior (OCB) dan Kualitas Kehidupan Kerja Terhadap Kinerja Pegawai BLUD Rumah Sakit Ibu dan Anak Provinsi Aceh Dengan Komitmen Organisasi Sebagai Variabel Intervening - Novita, Yenny (Jurnal Manajemen, 2024)
This study aimed to analyze the effect of job satisfaction, Organizational Citizenship Behavior and Quality of Work Life toward the employee performance of BLUD Women's and Children's Hospital of Aceh Province with the organizational commitment as an intervening variable. The research population is all employees of BLUD Mother and Child Hospital in Aceh Province with the number of 254 people. The total sample of 156. The data analysis method used is SEM (Structural Equation Modelling). The results showed that the job satisfaction, organizational citizenship behavior and quality of work life have a significant effect on the organizational commitment and employee performance. Organizational Commitment able to mediate the effect of the job satisfaction, organizational citizenship behavior and quality of work life toward the employee performance is partially.